Social Support Network for Senior Open University Program for Senior College of Arts, Sciences and Humanities, University of São Paulo, Brazil - Domingues, Marisa Accioly (2013)
The aim of the study is to describe the social support network of participants from the Third Age Open University, School of Arts, Sciences and Humanities of the University of Sao Paulo. Methods: The study was cross sectional, with a population of 117 elderly. Data were collected using a sociodemographic questionnaire and the instrument graphics Minimum Map of Elderly Affairs (MMRI), which identifies the size of the social support network, establishing levels of social support from the frequency of contacts received, for the functions assessed: visits, companionship, help in household chores, personal care and financial assistance. Seniors who participated in the study agreed with that by signing an informed consent and informed consent. Data were entered in the program Epidata and statistically analyzed using SPSS, version 17.0 Results: Most women (78%), married (53%), retired (82%) with mean age of 65.32 (SD = 7.02). Predominance of social support was of medium size, characterized by 16.80 (SD = 4.48). Stratified by age, older people had smaller social network and fewer social contacts. Elderly patients with stable compared to the unmarried, had larger social support network. Correlating data on age, income, social supports, it was observed that the higher family income, greater social support network. The results show that the social support decreases with the aging process. The variables of income and marital status factors act as modulators, contributing to the maintenance or decline of the network of relationships.